Forecasting the export volume of Surkhandarya region based on the ARIMA model - Khurramov Ramazon Allayor oglu (THE INNOVATION ECONOMY, 2026)
In this article, the volume of goods exports of Surkhandarya region is forecasted using ARIMA models until 2030